Isolation and Identification of Essential Oil Made From Kisar Sweet Orange Peels - Gelora Helena Augustyn; Anthonia Matjora; Vita N Lawalata; Sophia G Sipahelut (Tropical Small Island Agriculture Management, 2021)
Kisar sweet orange is an endemic fruit and primary commodity from Kisar Island, Southwest Maluku Regency - Maluku Province. Currently, Kisar sweet orangeswere only consumed as fresh fruit during this time, partially processed into juice and the peels were discarded as wastes. Kisar sweet orange peels can be processed into essential oil to increase their economic value. The essential oil made from orange peels is highly preferable, especially for the middle to upper-class consumers, for health and air-freshening purposes. This essential oil has a higher selling value. This research aims at isolating and identifying the chemical components and quality of essential oil made from Kisar sweet orange peels. This essential oil was isolated using a steam distillation method, and its chemical components were identified using GC-MS instruments.. The research results showed that the essential oil made from Kisar sweet orange peels dried with a cabinet dryer for two days utilizing the steam distillation method provides a yield of 0.53%, with its properties of specific gravity of 0.8457, refractive index of 1.4651 (20Â°C), acid number of 1.92, ester number of 8.05, and solubility in alcohol of 1:9. The main chemical component of the essential oil made from Kisar sweet orange peels detected by GC-MS is limonene (70.80%).